Supervised and self-directed technology-based dual-task exercise training programme for older adults at risk of falling - Protocol for a feasibility study. - Prerna Mathur; Helen Thomas; Angela Cooper; Magdalena Chechlacz; Afroditi Stathi; Victoria Goodyear; Caroline Miller; Taylor Krauss; Natalie Ives; Laura Magill; Philip Kinghorn; Daisy Wilson; et al. (PLoS ONE)
Falls among older adults pose a significant public health challenge, as they lead to severe outcomes such as fractures and loss of independence. Research has shown that training cognitive function and balance simultaneously, termed Dual-Task (DT) training, improves mobility and reduces fall risks in older adults. This study aims to evaluate the feasibility and acceptability of a blended supervised and self-directed technology-based DT training programme for older adults who have high risk of falling. This is a single-arm, non-randomised feasibility study employing quantitative and qualitative methods. Fifty healthy adults aged 65 years or above will be recruited from the NHS primary and secondary care pathways and from the community. Participants will undergo supervised cognitive and balance DT training for 12 weeks, followed by self-directed DT training for an additional 12 weeks. The cognitive training will be delivered using a commercial mobile application (app) available from the AppStore or Google Play. The balance training will involve static (Marching on the spot, Tandem Stand, Hip Abduction & Extension, Squats, Tiptoe Stand, and Pendulum/Sideways Sway) and dynamic (Figure of Eight Walk, Walking Forwards and Backwards, Lunges, Functional Reach, Toe Tapping, Upper Limb Strength Exercises, and Side-Steps/Simple Grapevine) exercises focused on improving balance, postural stability and strength. Feasibility outcomes will be recruitment, adherence, usage of the app, and attrition. Outcomes measure data, that will be collected at baseline and at 24 weeks, includes the Timed- Up and Go (TUG) test (likely primary outcome in any future trial), along with self-reported questionnaires assessing cognition, fear of falling, quality of life, healthcare service usage, and the self-reported number of falls. Focus group interviews will be conducted with thirty participants and thirty healthcare professionals for in-depth exploration of the feasibility and acceptability of the DT training programme.